Green Investment Regime: Judul: Analysis of the Implementation of Green Economy-Based Maritime Tourism Village Potential Development - Muh. Zainuddin Badollahi; Siti Hajar N. Aepu; Risma Ariyani (Journal La Bisecoman, 2022)
In this study, we delve into the concept of the "Green Economy," aiming to achieve a harmonious balance between economic growth and environmental preservation. We offer practical recommendations for various stakeholders, including stakeholders, the community, and the Sinjai Regency government. To stakeholders, we advocate for an increased adoption of the green economy concept in the development of marine tourism in Sinjai Regency, with the potential to enhance local economic growth and alleviate poverty. We also encourage the community to collectively embrace cleanliness and environmental stewardship, as it represents a shared responsibility for sustainability. Simultaneously, we suggest that the Sinjai Regency government improve facilities and infrastructure at tourist destinations to provide an enhanced experience for visitors. Through these measures, we aspire to achieve sustainable economic growth and safeguard the natural splendor of Sinjai Regency for generations to come.